2021
DOI: 10.3390/ijms22157883
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyphosphorylation on Behavior of Protein Disordered Regions

Abstract: Proteins interact with many charged biological macromolecules (polyelectrolytes), including inorganic polyphosphates. Recently a new protein post-translational modification, polyphosphorylation, or a covalent binding of polyphosphate chain to lysine, was demonstrated in human and yeast. Herein, we performed the first molecular modeling study of a possible effect of polyphosphorylation on behavior of the modified protein using replica exchange molecular dynamics simulations in atomistic force field with explici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Regardless, it will now be important to learn how the addition of long polyphosphate chains to an already highly-charged and intrinsically disordered loop is harnessed to regulate protein function. A current computational analysis provides some insight: modeling the polyphosphorylation of the disordered linker region of Hsp70 impacts both the conformation ensemble of the IDR, and its interaction potency, implying that both inter- and intra-molecular interactions may change upon lysine polyphosphorylation 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, it will now be important to learn how the addition of long polyphosphate chains to an already highly-charged and intrinsically disordered loop is harnessed to regulate protein function. A current computational analysis provides some insight: modeling the polyphosphorylation of the disordered linker region of Hsp70 impacts both the conformation ensemble of the IDR, and its interaction potency, implying that both inter- and intra-molecular interactions may change upon lysine polyphosphorylation 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, it will now be important to learn how the addition of long polyphosphate chains to an already highly charged and intrinsically disordered loop is harnessed to regulate protein function. A current computational analysis provides some insight: modeling the polyphosphorylation of the disordered linker region of Hsp90 impacts both the conformation ensemble of the IDR, and its interaction potency, implying that both inter‐ and intramolecular interactions may change upon lysine polyphosphorylation [33].…”
Section: Discussionmentioning
confidence: 99%
“…34,35 It was envisaged that the imine bond plays a key role in the anticancer activity, due to the fact that its dynamic character favors the binding of amino acids which are essential for the growth of tumor cells. [36][37][38] Moreover, some studies indicated that the presence of hydroxyl units in the proximity of imine linkage improves the anticancer activity, by a synergistic antioxidant activity. 39,40 Bringing all this information together, the idea of binding betulin with imine units towards achieving new anticancer agents appears to be very promising.…”
Section: Introductionmentioning
confidence: 99%